2008
DOI: 10.1523/jneurosci.0744-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes Are the Major Vesicular Compartment Undergoing Ca2+-Regulated Exocytosis from Cortical Astrocytes

Abstract: Although Ca 2ϩ-dependent exocytosis is considered to be a pathway for gliotransmitter release from astrocytes, the structural and functional bases of this process remain controversial. We studied the relationship between near-membrane Ca 2ϩ elevations and the dynamics of single astroglial vesicles with styryl (FM) dyes. We show that cultured astrocytes, unlike neurons, spontaneously internalize FM dyes, resulting in the labeling of the entire acidic vesicle population within minutes. Interestingly, metabotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
177
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(193 citation statements)
references
References 65 publications
13
177
0
3
Order By: Relevance
“…11,12,20,44 We show that astrocyte cell membrane injury causes a greater [Ca 2+ ] c increase, triggering more robust lysosome exocytosis. Receptor stimulation causes a sustained and low rate of exocytosis where lysosomes release a part of their luminal content and none of their membrane proteins (Figures 2 and 6).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…11,12,20,44 We show that astrocyte cell membrane injury causes a greater [Ca 2+ ] c increase, triggering more robust lysosome exocytosis. Receptor stimulation causes a sustained and low rate of exocytosis where lysosomes release a part of their luminal content and none of their membrane proteins (Figures 2 and 6).…”
Section: Discussionmentioning
confidence: 67%
“…29,34 However, the existence of partial exocytosis of astrocyte lysosomes has been contested. 11,20 Using FITC dextran to label the lysosome lumen, we found that astrocyte lysosomes can exocytose their contents partially (Figure 2c) or fully (Figure 2d). In fibroblasts, lysosomes that partially release their contents have a restricted fusion pore that allows the release of smaller (10 kDa), but not larger (500 kDa) sized dextran.…”
Section: Resultsmentioning
confidence: 96%
“…42,43 In addition, the core secretory machinery for vesicle exocytosis consists of SNAREs (N-ethylmaleimide-sensitive factor attachment protein receptors) and sec1/STXBP/Munc18-like proteins. 44 The marker protein of secretory lysosomes as the major vesicular compartment for Ca 2C -regulated exocytosis from astrocytes 45 is VAMP7/TI-VAMP (vesicle associated membrane protein 7). 46 Verderio et al (2012) 47 report that VAMP7 is the SNARE of secretory lysosomes contributing to ATP secretion from astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Short exposure of mouse cortical astrocytes in culture to micromolar concentrations of FM4-64 (6.7 M, 2 min) at room temperature (RT) followed by a 10-min wash showed the expected FM4-64 puncta (14,18,19) associated with a diffuse labeling. Rupturing the PM in zero extracellular Ca 2ϩ concentration ([Ca 2ϩ ] o ) reduced the diffuse labeling without affecting the puncta (Fig.…”
Section: Endocytosis Is Not a Major Mechanism For Astrocytic Fm4-64 Umentioning
confidence: 99%
“…Cultured astrocytes internalize FM dyes (3,(12)(13)(14)(15)(16)(17)(18). However, this uptake is not modified by the activation of metabotropic glutamate receptors (19), and its mechanism remains elusive.…”
mentioning
confidence: 99%